An update on pathogenesis of psoriatic arthritis and potential therapeutic targets. (3rd August 2019) - Chimenti, Maria Sole; Triggianese, Paola; De Martino, Erica; Conigliaro, Paola; Fonti, Giulia Lavinia; Sunzini, Flavia; Caso, Francesco; Perricone, Carlo; Costa, Luisa; Perricone, Roberto
ABSTRACT: Introduction : Innate immune response and bone remodeling are key factors contributing to the pathogenesis of psoriatic arthritis (PsA). Moreover, the evidence of autoantibodies in patients' sera suggests an autoimmune side in PsA. Besides the immune pathways, studies strongly support the role of genetic risk alleles in affecting the clinical heterogeneity of PsA as well as the response to therapy. A good clinical response to treatment, indeed, represents a challenge in PsA patients and the identification of patient-targeted therapies is still a critical issue. Areas covered : We performed a systematic review aiming at describing new evidence on PsA pathogenesis and treatments. Reported items for systematic reviews (PRISMA checklist) were analyzed. Studies included from the PubMed database addressed the following items: innate immunity, autoimmunity, bone remodeling, and therapeutic targets in PsA; time frame of research 1970–2019. Specifically, we reviewed data on IL-17 inhibitors, abatacept, JAK inhibitors, ABT 122, and A (3) adenosine receptors agonist, CF101. Expert opinion : In PsA an intriguing pathogenetic network has been documented. Several biological and synthetic drugs are promising in terms of efficacy and safety profile.